The Nature of the Social Firm: Alternative Organizational Forms for Social Value Creation and Appropriation - Lazzarini, Sergio G. (Academy of Management Review, 2020)
I assess how alternative organizational forms affect the ability of multiple actors to appropriate economic rents in activities expected to create social value—defined as broad social benefits to a given population (including more vulnerable groups) minus their associated provision costs. I simultaneously examine three stylized forms: public bureaucracy, involving both public sponsorship and public management; public–private partnerships, with a mix of public sponsorship and private management; and social enterprise, with both private management and sponsorship from impact-oriented investors. Although the extant literature has underscored a supply-side hazard emerging when actors try to appropriate rents by economizing on noncontractible social dimensions, I also examine the implications of a demand-side tradeoff emerging when providers are tempted to focus on more profitable customer segments and exclude more vulnerable populations. In my framework, distinct organizational forms change the managerial incentives to provide inclusive, high-quality social services based on three main factors: the relative attractiveness of beneficiary segments, their cost structure, and the extent of fixed costs to implement and operate services. I thus offer a testable theory of organizational alignment, identifying the comparative merits of each form based on how they incentivize public and private actors to create and appropriate social value.